To Complete: the statement (RW)/?=(ZR)/?=(WZ)/? in the figure shown,Given:Figure is shown below.12210202811.jpg

Nann 2021-02-11 Answered

To Complete: the statement RW?=ZR?=WZ? in the figure shown,
Given:
Figure is shown below.
image

You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

faldduE
Answered 2021-02-12 Author has 109 answers
Calculation:
In RWZandZWS.
WRZ=WZS(Given)
W=W(Common)
WZ=WZ(Common)
By AAS similarity, RWZZWS.
Therefore,
RWZW=ZRSZ=WZWS
Therefore, the answer is ZW, SZ and WS.
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2021-05-17

Find the point on the line y=2x+3 that is closest to the origin.

asked 2022-07-21
Is there an easier way to solve a "Find the locus" problem?
Note: I am not concerned with the accuracy of my solution so you don't need to redo any of my calculations.
Original question: Suppose ABC is an equilateral triangular lamina of side length unity, resting in two-dimensions. If A and B were constrained to move on the x- and y-axis respectively, then what is the locus of the centre of the triangle?
My solution: Let the vertices of Δ A B C be A = ( x 0 , 0 ), B = ( 0 , y 0 ) and C = ( x , y ). Let the centre of the triangle be D = ( X , Y ). We wish to find the locus of D under the constraints:
x 0 2 + y 0 2 = 0 ( x x 0 ) 2 + y 2 = 0 x 2 + ( y y 0 ) 2 = 0
Since D is the centre of the triangle, we know
X = x + x 0 3 and Y = y + y 0 3
Parametrizing: Let θ be the angle that the edge AB makes with the x-axis. We use (theta) as our parameter of choice to write, x 0 = cos θ y 0 = sin θ
for θ [ 0 , 2 π )
This implies, ( x cos θ ) 2 + y 2 = 0
We can parametrize this with another parameter ϕ [ 0 , 2 π ) as
x = cos θ + cos ϕ y = sin ϕ
Plugging these back into third equation gives
( cos θ + cos ϕ ) 2 + ( sin ϕ sin θ ) 2 = 1
After lots of algebraic manipulations...
X = 1 2 cos θ ± 1 2 3 sin θ Y = 1 2 sin θ ± 1 2 3 cos θ
asked 2022-07-25
For a triangle ABC, prove that angle C is a right angle if and only if the median of side c is c/2
asked 2020-11-12
For the following statement, either prove that they are true or provide a counterexample:
Let a, b, m, nZ such that m, n > 1 and nm. If ab(modm), then
ab(modn)
asked 2022-08-09
Finding the volume of revolution using the method of shells
I'm trying to find the volume of the solid generated by revolving the region bounded by y = x 2 and y = 6 x + 7 about x-axis using the shell method. I applied the method and I got 15864/5 multiplied by π but it's not correct.
Details: I integrated 1 49 y ( y y 7 6 ) d y
asked 2021-02-16

Consider the line represented by the equation 5x+2y=10. How is the slope of the line related to values of A, B, and C in standard form Ax+By=C?

asked 2022-07-17
Mathematically prove that a Beta prior distribution is conjugate to a Geometric likelihood function
I have to prove with a simple example and a plot how prior beta distribution is conjugate to the geometric likelihood function. I know the basic definition as
'In Bayesian probability theory, a class of distribution of prior distribution θ is said to be the conjugate to a class of likelihood function f ( x | θ ) if the resulting posterior distribution is of the same class as of f ( θ ).'
But I don't know how to prove it mathematically.

New questions